Alleviation of Zn toxicity by low water availability - Disante, Karen B; Cortina, Jordi; Vilagrosa, Alberto; Fuentes, David; Hernández, Encarni I; Ljung, Karin (Physiologia Plantarum, 2013)
Heavy metal contamination and drought are expected to increase in large areas worldwide. However, their combined effect on plant performance has been scantly analyzed. This study examines the effect of Zn supply at different water availabilities on morpho-physiological traits of Quercus suber L. in order to analyze the combined effects of both stresses. Seedlings were treated with four levels of zinc from 3 to 150 µM and exposed to low watering (LW) or high watering (HW) frequency in hydroponic culture, using a growth chamber. Under both watering regimes, Zn concentration in leaves and roots increased with Zn increment in nutrient solution. Nevertheless, at the highest Zn doses, Zn tissue concentrations were almost twice in HW than in LW seedlings. Functional traits as leaf photosynthetic rate and root hydraulic conductivity, and morphological traits as root length and root biomass decreased significantly in response to Zn supply. Auxin levels increased with Zn concentrations, suggesting the involvement of this phytohormone in the seedling response to this element. LW seedlings exposed to 150 µM Zn showed higher root length and root biomass than HW seedlings exposed to the same Zn dose. Our results suggest that low water availability could mitigate Zn toxicity by limiting internal accumulation. Morphological traits involved in the response to both stresses probably contributed to this response.
APS
Keywords: Drought; functional traits; Heavy metals; Quercus suber L.

Perspectives in dryland restoration: approaches for climate change adaptation - Ramón Vallejo, V.; Smanis, Athanasios; Chirino, Esteban; Ramo, V.; Fuentes, David; Valdecantos, Alejandro; Vilagrosa, Alberto (New Forests, 2012)
Reforestation efforts in dryland ecosystems frequently encounter drought and limited soil productivity, although both factors usually interact synergistically to worsen water stress for outplanted seedlings. Land degradation in drylands (e.g. desertiﬁcation) usually reduces soil productivity and, especially, soil water availability. In dry sub-humid regions, forest ﬁres constitute a major disturbance affecting ecosystem dynamics and reforestation planning. Climate change projections indicate an increase of drought and more severe ﬁre regime in many dryland regions of the world. In this context, the main target of plantation technology development is to overcome transplant shock and likely adverse periods, and in drylands this is mostly related to water limitations. In this paper, we discuss some selected steps that we consider critical for improving success in outplanting woody plants, both under current and projected climate change conditions including: (1) Plant species selection, (2) Improved nursery techniques, and (3) Improved planting techniques. The number of plant species used in reforestation is increasing rapidly, moving from a reduced set of well-known, easy-to-grow, widely used species, to a large variety of promising native species. Available technologies allow for reintroducing native plants and recovering critical ecosystem functions for many degraded drylands. However, climate change projections introduce large uncertainties about the sustainability of current reforestation practices. To cope with these uncertainties, adaptive restoration approaches are suggested, on the basis of improved plant quality, improved techniques for optimizing rain use efﬁciency in plantations, and exploring native plant species, including provenances and genotypes, for their resilience to ﬁre and water use efﬁciency.
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: Mediterranean ecosystems; Nursery cultivation; Reforestation; Species selection; Water harvesting

Response to drought of Zn-stressed Quercus suber L. seedlings - Disante, Karen B; Fuentes, David; Cortina, Jordi (Environmental and Experimental Botany, 2011)
Zinc is an essential nutrient for higher plants but it becomes toxic as its availability increases. In nature, different stress factors commonly occur concurrently, challenging our ability to predict their impacts. Information on zinc (Zn) effect on plant ability to withstand other sources of stress is scarce. This study examines the effect of zinc supply rate on the response of Quercus suber L. seedlings to water stress. Seedlings were treated with four levels of zinc from 3 to 150 M, and then exposed to a short severe drought. Zinc concentration in leaves and roots increased with zinc availability. Maximum photosynthetic rate, photochemical efﬁciency, root length and speciﬁc root length decreased as Zn availability increased. The decrease was particularly intense between 50 and 150 M Zn. The relative effects of drought were less intense in seedlings receiving higher doses of Zn than in those receiving 3 M. Thus, at severe drought, relative water content of detached leaves decreased to 52% in seedlings receiving the lowest level of Zn. In contrast, relative water content remained above 70% in seedlings exposed to high concentrations of this metal. The pattern was similar for photosynthetic rate and stomatal conductance, as the decrease in these variables resulting from severe drought was 100% and 90% in seedlings receiving 3 M and 65% and 56% in seedlings receiving the highest Zn dose. Our results suggest that morpho-physiological responses to zinc may foster water conservation strategies and alleviate the effects of drought in the short term, but they may impair seedling ability to root and grow in a longer term
Keywords: growth response; Heavy metal; Relative water content; water use efﬁciency

Prospective use of collected fog water in the restoration of degraded burned areas under dry Mediterranean conditions - Estrela, María J.; Valiente, José a.; Corell, David; Fuentes, David; Valdecantos, Alejandro (Agricultural and Forest Meteorology, 2009)
A mountainous plot located in the interior of the Valencia region (east coast of the Iberian Peninsula) was identiﬁed for reforestation using the fog-water collection potential prevailing in the area. Fog data were obtained by means of an instrument ensemble consisting of a passive cylindrical fog-water collector, a rain gauge, a wind direction and velocity sensor and a temperature and humidity probe. Preliminary results gave rise to the additional deployment of a low-cost 18-m2 ﬂat-panel collector connected to three 1000-l tanks for larger scale fog-water collection and storage. The 2007 annual rate of fog water that could be derived from the instrument ensemble amounted to 3.3 l/m2 /day, which turn out to ﬁll up the storage tanks completely in only 5 months, even though the ﬂat-panel collector could not be operative 100% of the time. The study made use of the in situ stored water and a micro-irrigation network to irrigate a plot of reforestation seedlings through small water pulses localized deep in the planting hole during the summer dry period. Until the present, this forest location had always shown a difﬁcult self-recovery due to the high level of land degradation resulting from recurrent forest ﬁres in the past. Results indicate that survival rates and seedling performance of the two species planted, Pinus pinaster and Quercus ilex, improved with the use of small timely waterings and additional treatments with composted biosolid.
Keywords: Micro-irrigation; passive fog collection; Reforestation; Valencia region

Prospective use of collected fog water in the restoration of degraded burned areas under dry Mediterranean conditions - Estrela, María J.; Valiente, José a; Corell, David; Fuentes, David; Valdecantos, Alejandro (Agricultural and Forest Meteorology, 2009)
A mountainous plot located in the interior of the Valencia region (east coast of the Iberian Peninsula) was identiﬁed for reforestation using the fog-water collection potential prevailing in the area. Fog data were obtained by means of an instrument ensemble consisting of a passive cylindrical fog-water collector, a rain gauge, a wind direction and velocity sensor and a temperature and humidity probe. Preliminary results gave rise to the additional deployment of a low-cost 18-m2 ﬂat-panel collector connected to three 1000-l tanks for larger scale fog-water collection and storage. The 2007 annual rate of fog water that could be derived from the instrument ensemble amounted to 3.3 l/m2 /day, which turn out to ﬁll up the storage tanks completely in only 5 months, even though the ﬂat-panel collector could not be operative 100% of the time. The study made use of the in situ stored water and a micro-irrigation network to irrigate a plot of reforestation seedlings through small water pulses localized deep in the planting hole during the summer dry period. Until the present, this forest location had always shown a difﬁcult self-recovery due to the high level of land degradation resulting from recurrent forest ﬁres in the past. Results indicate that survival rates and seedling performance of the two species planted, Pinus pinaster and Quercus ilex, improved with the use of small timely waterings and additional treatments with composted biosolid.
Keywords: Micro-irrigation; passive fog collection; Reforestation; Valencia region